Migratory adaptations in Chrysoperla sinica (Neuroptera: Chrysopidae) - Liu, Z; Wyckhuys, Kris A.G.; Wu, K (Oxford University Press, 2011)
The green lacewing Chrysoperla sinica (Tjeder) (Neuroptera: Chrysopidae) is a common natural enemy of various insect pests in China and is frequently employed for augmentation biological control. Adults of this species perform migration flights after emergence, the nature of which affects its value for biological control program. In this manuscript, we report characteristics of C. sinica migratory populations captured during 2008 2009 using a light trap at Beihuang Island (Bohai Gulf), 40 60 km from mainland China, and their relationships with flight performance. In total, 1,452 migratory C. sinica adults were caught for these 2 yr. Throughout the sampling period, migratory populations consisted of >50% female individuals, most of which were in preoviposition period and had low degrees of ovarian development. During autumn, most migratory females were unmated. C. sinica females began oviposition since 7 d after emergence. Flight mill tests showed that 5-d-old females in preoviposition period flew over the longest distance (i.e., 4.50 ± 1.31 km) over 8 h and mating status did not affect flight performance. For 3-d-old individuals, males flew over larger distances than females, and unmated individuals exhibited stronger flight capability than mated ones. Hence, gender, mating status, and age all determine C. sinica flight performance. Based upon those findings, we can indicate that C. sinica migratory populations appear adapted to long-distance flights. This research should help understand C. sinica population dynamics and aid its incorporation within integrated pest management (IPM) packages for several crops.